Accountability of Layanan Dasar by school counselor in junior high school in East Jakarta on school principals perspective - Badrujaman, Aip; Luawo, Meithy Intan Rukia; Cahyawulan, Wening (Konselor, 2018)
The objective of this research is to describe of the accountability of Layanan Dasar school counselor on school principals’ perspective. The study used descriptive study methods, used sampling technique was convenience sampling with a sample of 33 school principals, and instruments used were Mixed Standard Scale for Evaluating Student Behavior and analysis data used descriptive. The results of the study show that overall the level of accountability of guidance and counseling programs in schools in East Jakarta is at a low level (49%). Second, achievements based on indicators are not significantly different (10%). Third, the highest indicator of accountability is the responsibility, while the lowest indicator is the feedback mechanism. Fourth, each school falls into the low category of 50%, medium 30%, and high 20%. Based on the results there needs to be an effort to improve the accountability of the guidance and counseling program and base of feedback mechanism indicators, teacher Guidance and counseling must create a mechanism by which the principal can submit input.